Preparation of Sn-NiO films and all-solid-state devices with enhanced electrochromic properties by magnetron sputtering method. (20th January 2021) - Zhao, Yingming; Zhang, Xiang; Chen, Xi; Li, Wenjie; Wang, Lebin; Li, Zitong; Zhao, Jiupeng; Endres, Frank; Li, Yao
Abstract: In this paper, Sn-NiO films for a superior electrochromic performance were prepared by a simple one-step magnetron sputtering process. The amount of Sn in the Sn-NiO films was controlled by adjusting the sputtering power of the SnO2 target. The modification of the microstructure of the NiO film by Sn 4+ ions refined the grain size, enlarged the electrochemically active surface and promoted the diffusion of lithium ions, thereby enhancing the electrochromic performances of a NiO film. Compared to pure NiO, the Sn-NiO film prepared at a 10 W sputtering power of SnO2 target obtained outstanding electrochromic performances, including large transmittance modulation (65.1%), high coloration efficiency (39.3 cm 2 ·C − 1 ), fast switching speed (1.3 s and 1.4 s) and good cycling durability at a wavelength of 550 nm. Besides, an optimized Sn-NiO film was used as an anodic electrochromic layer to prepare inorganic all-solid-state electrochromic device (ECD) and the ECD displayed excellent electrochromic performance. The strategy of preparing NiO modified by Sn 4+ ions presents an innovative direction to obtain high-performance electrochromic materials for energy-saving smart windows.